Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/ange.201403410
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Allylic Alkylation of Simple Ketones with Allylic Alcohols and Its Mechanistic Study

Abstract: Allylic alcohols were directly used in Pd-catalyzed allylic alkylations of simple ketones under mild reaction conditions. The reaction proceeded smoothly at 20 8C by the concerted action of a Pd catalyst, a pyrrolidine co-catalyst, and a hydrogen-bonding solvent, and does not require any additional reagents. A computational study suggested that methanol plays a crucial role in the formation of the p-allylpalladium complex by lowering the activation barrier.The palladium-catalyzed allylic alkylation is a powerf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Hydrogen-bond-driven activation of allylic ethers has been previously reported in methanol. 21 DFT calculations showed that hydrogen bonding could lower the activation energy by more than 20 kcal/mol. 21 In the oxidative addition step, the counteranion may be rapidly exchanged from the phenolic oxide anion to a phosphate ion (Figure 4c).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen-bond-driven activation of allylic ethers has been previously reported in methanol. 21 DFT calculations showed that hydrogen bonding could lower the activation energy by more than 20 kcal/mol. 21 In the oxidative addition step, the counteranion may be rapidly exchanged from the phenolic oxide anion to a phosphate ion (Figure 4c).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…22 In addition to the kinetic studies, mechanistic investigations have elucidated the structures of actual catalysts. For example, (π-allyl)palladium with two phosphine ligands is generally considered a key intermediate, 21 but the complex with a single phosphine may be more reactive. 23,24 Palladium dimers have also been shown to be active catalysts in some instances.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among the many transition metals used in allylic alkylations, palladium is generally recognized as the most versatile metal due to its ability to catalyze a variety of different reactions. In early reports, stabilized carbanions such as malonates were generally used as nucleophiles, but more recently, nonstabilized enolates of esters, amides, and ketones have received more attention . The decarboxylative allylic alkylation of ketones has found widespread applications.…”
mentioning
confidence: 99%
“…The employment of allylic alcohols in the α-allylic alkylation by combined catalysis (enamine and transition metal catalysis) has also been expanded by several other groups [31]. For example, Bandini et al [32] used gold as the co-catalyst, Yasuda et al [33] and Yoshida et al [34, 35] used palladium as co-catalyst, and Zhou et al [36] employed β-ketocarbonyl compounds as substrates.…”
Section: α-Allylic Alkylation Of Aldehydes and Ketonesmentioning
confidence: 99%